Diffusion tensor imaging of cingulum bundle and corpus callosum in schizophrenia vs. bipolar disorder. (30th August 2017) - Nenadić, Igor; Hoof, Anna; Dietzek, Maren; Langbein, Kerstin; Reichenbach, Jürgen R.; Sauer, Heinrich; Güllmar, Daniel
Abstract: Both schizophrenia and bipolar disorder show abnormalities of white matter, as seen in diffusion tensor imaging (DTI) analyses of major brain fibre bundles. While studies in each of the two conditions have indicated possible overlap in anatomical location, there are few direct comparisons between the disorders. Also, it is unclear whether phenotypically similar subgroups (e.g. patients with bipolar disorder and psychotic features) might share white matter pathologies or be rather similar. Using region-of-interest (ROI) analysis of white matter with diffusion tensor imaging (DTI) at 3 T, we analysed fractional anisotropy (FA), radial diffusivity (RD), and apparent diffusion coefficient (ADC) of the corpus callosum and cingulum bundle in 33 schizophrenia patients, 17 euthymic (previously psychotic) bipolar disorder patients, and 36 healthy controls. ANOVA analysis showed significant main effects of group for RD and ADC (both elevated in schizophrenia). Across the corpus callosum ROIs, there was not group effect on FA, but for RD (elevated in schizophrenia, lower in bipolar disorder) and ADC (higher in schizophrenia, intermediate in bipolar disorder). Our findings show similarities and difference (some gradual) across regions of the two major fibre tracts implicated in these disorders, which would be consistent with a neurobiological overlap of similar clinical phenotypes. Highlights: Schizophrenia and (psychotic) bipolar disorder share phenotypic features. DTI was analysed for corpus callosum and cingulum for both disorders. Schizophrenia patients show higher cingulum diffusivity, but not fractional anisotropy. In corpus callosum radial diffusivity is higher in schizophrenia, but lower in bipolar disorder. Schizophrenia and bipolar disorder diverge in indicators of white matter pathology.